2017
DOI: 10.1055/s-0037-1603802
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Sepsis: Clinical Considerations

Abstract: Unspecific symptoms and rapid development of sepsis up to septic shock from systemic inflammatory response syndrome (SIRS) are well-known, important issues in neonatology. A common cause is the infection by Streptococcus agalactiae (Group B Streptococcus [GBS]) or Escherichia coli, which contributes significantly to neonatal morbidity and mortality. Whereas early-onset sepsis is normally derived from mother during birth, late-onset sepsis can be transmitted by the environment. Management of neonatal sepsis inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Prematurity: In our population, 76,4% (117) of neonates were premature, a result that is similar with the ones found in Naulikha et al study, with a proportion of 89,1 % and in Betty C. et al study where 80,6% of neonates were premature [3,12]. Another study conducted also in Austria comparing GBS to E. coli in EOS found that 42% of neonates with GBS EOS were premature and that 72,7% of neonates with E. coli EOS were premature [23].…”
Section: Infant Risk Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…Prematurity: In our population, 76,4% (117) of neonates were premature, a result that is similar with the ones found in Naulikha et al study, with a proportion of 89,1 % and in Betty C. et al study where 80,6% of neonates were premature [3,12]. Another study conducted also in Austria comparing GBS to E. coli in EOS found that 42% of neonates with GBS EOS were premature and that 72,7% of neonates with E. coli EOS were premature [23].…”
Section: Infant Risk Factorssupporting
confidence: 91%
“…3,2% (5) were admitted for fever and 4,3% (7) for neurological distress. Other signs were seen too such as hemorrhage syndrome in 7,1% (11), low sucking reflex in 14,4% (23), sclerema in 3% (5), apnea in 9% (14), tachycardia in 22,2% (34) and jaundice in 7,8% (12), hypothermia in 47 % (72), Hyperglycemia was found 13,70% (21) and hypoglycemia in 9,1% (14) of cases. 13,07% (20) had oliguria and 2,4% (4) had anuria.…”
Section: Neonates' Clinical Presentationmentioning
confidence: 98%
See 1 more Smart Citation